Race weight: perceptions of elite female road cyclists - Haakonssen, E. C.; Martin, D. T.; Jenkins, D. G.; Burke, L. M. (International Journal of Sports Physiology and Performance, 2015)
Purpose: This study investigated the satisfaction of elite female cyclists with their body weight (BW) in the context of race performance, the magnitude of BW manipulation, and the association of these variables with menstrual function. Methods: Female competitors in the Australian National Road Cycling Championships (n = 32) and the Oceania Championships (n = 5) completed a questionnaire to identify current BW, BW fluctuations, perceived ideal BW for performance, frequency of weight consciousness, weight-loss techniques used, and menstrual regularity. Results: All but 1 cyclist reported that female cyclists are "a weight-conscious population," and 54% reported having a desire to change BW at least once weekly; 62% reported that their current BW was not ideal for performance. Their perceived ideal BW was (mean ± SD) 1.6 ± 1.6 kg (2.5% ± 2.5%) less than their current weight (P < .01), and 73% reported that their career-lowest BW was either "beneficial" or "extremely beneficial" for performance. 65% reported successfully reducing BW in the previous 12 months with a mean loss of 2.4 ± 1.0 kg (4.1% ± 1.9%). The most common weight-loss technique was reduced energy intake (76%). Five cyclists (14%) had been previously diagnosed as having an eating disorder by a physician. Of the 18 athletes not using a hormonal contraceptive, 11 reported menstrual dysfunction (oligomenorrhea or amenorrhea). Conclusion: Elite Australian female cyclists are a weight-conscious population who may not be satisfied with their BW leading into a major competition and in some cases are frequently weight conscious.